Shiitake (Lentinula edodes (Berkeley) Pegler) extracts as a modulator of micronuclei induced in HEp-2 cells - Miyaji, C. K.; Poersch, A.; Ribeiro, L. R.; Eira, A. F.; Colus, I. M. S. (Elsevier B.V., 2006)
Shiitake (Lentinula edodes (Berkeley) Pegler) is one of the most consumed mushrooms, for both therapeutic purposes and as food, therefore, the study of its biological properties is of great interest for producers and consumers. Aqueous extracts of the shiitake mushroom (L. edodes (Berkeley) Pegler) were evaluated by the micronucleus test (MN) in HEp-2 cells in vitro, to analyze their possible mutagenic and antimutagenic activities. None of the three extract concentrations tested (0.5, 1.0 and 1.5 mg/mL) presented mutagenicity at any of the preparation temperatures (4 degrees C, 22 +/- 2 degrees C and 60 degrees C). In the antimutagenicity evaluation, all extract concentrations at all preparation temperatures presented a strong protective activity for the HEp-2 cells in response to the alkylating agent methyl methanesulfonate (MMS) in the different treatment protocols: pre-treatment, simultaneous treatment and post-treatment. The extracts prepared at 22 +/- 2 degrees C presented the lowest frequencies of MN in the evaluations of mutagenicity and antimutagenicity, indicating these as the best option for potential therapeutic use. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: micronucleus test; Lentinula edodes; Shiitake; mutagenicity; antimutagenicity